Death by landscape essays - Wilk, Elvia 1989- (Soft Skull, 2022)
"This collection is about love, death, plants, and weird fiction. It takes its title from a Margaret Atwood story in which an adolescent girl seems to turn into a tree. It examines works by Doris Lessing, Jenny Hval, Anne Carson, Octavia Butler, Michelle Tea, Helen Phillips, Mark Fisher, Donna Haraway, and Jeff and Ann VanderMeer; it explores the erotics of compost, vampire-themed live-action roleplaying, intoxicated birds, medieval nuns, invasive spores, and solarpunk. The book asks: what kind of stories are being written that help us rethink our human-centric perspective of Earth? What kinds of narratives will make sense of the age of extinction? Death by Landscape creates a syllabus for feminist sci-fi and speculative fiction for our time"--
Includes bibliographical references.
Keywords: American essays; SOCIAL SCIENCE / Popular Culture; LITERARY COLLECTIONS / Essays; LITERARY CRITICISM / Feminist; Essays